Formulation based predictive cure kinetics modelling of epoxy resins: dataset - Voto, Gabriele; Sequeira, Leela; Skordos, Alexandros A. (Cranfield University, 2021)
01.Binary blends.xlsm - it contains the integrated DSC data (i.e. time, temperature, conversion degree and reaction rate) and corresponding data resulting from the application of an autocatalytic model for all binary blends assessed across one dynamic and two isothermal profiles; it also includes the reaction rate errors between experiment and prediction. 02.Ternary blends.xlsm - it contains the integrated DSC data (i.e. time, temperature, conversion degree and reaction rate) and corresponding data resulting from the application of the Formulation Ratio Superposition (FRS) for all ternary blends assessed across one dynamic and two isothermal profiles; it also includes the reaction rate errors between experiment and prediction in columns labelled 'Rate error across wider dataset' which report reaction rate for a greater sampling rate.
Keywords: 'Cure matrix composition design'; 'Formulation Ratio Superposition'; 'Thermosetting resin'; 'Amine curative'; 'Cure kinetics'; 'Process modelling'; 'Composites manufacturing'; 'Organic Chemistry'; 'Reaction Kinetics and Dynamics'; 'Aerospace Materials'; 'Composite and Hybrid Materials'; 'Manufacturing Engineering not elsewhere classified'; 'Polymers and Plastics'; 'Simulation and Modelling'; 'Theory and Design of Materials'